Principles of Islamic Law - Dinda Suciana Rambe; Eviana Sagala (AT-TAFAHUM: Journal of Law, 2022)
This study aims to analyze the principles of Islamic law as the basic principles in the formation and application of law derived from the Qur'an, Hadith, and the ijtihad of scholars. The research method used is normative legal research with a statutory and conceptual approach, through a literature study of various primary, secondary, and tertiary legal sources. The results show that the principles of Islamic law play a crucial role in realizing the objectives of sharia (maqashid al-syari'ah), namely protecting religion, life, intellect, descendants, and property. These principles reflect fundamental values such as justice, benefit, legal certainty, and flexibility in facing current developments. Apart from that, there are special principles such as eliminating difficulties (nafyu al-haraj), reducing legal burdens (qillat al-taklif), and establishing laws in stages (tadarruj), which show that Islamic law is adaptive, humane, and not burdensome. The application of these principles makes Islamic law remain relevant in various social conditions in society. Thus, the principles of Islamic law not only function as a normative basis, but also as a practical guideline in creating laws that are just, balanced, and oriented towards the welfare of the people.